Features of legal regulation of labor relation of aviation personnel - A. V. Zhyla; A. O. Hordeiuk (Науковий вісник Ужгородського національного університету. Серія Право)
The author emphasizes the great importance of civil aviation as an industry that actively contributes to the development of the global and domestic economy of any country and points to the European integration processes that took place in Ukraine in peacetime and are continuing during wartime in this area. The author emphasizes the dominant mission of aviation personnel in providing flight safety and the need for their training and retraining even in difficult situations, which is important for the resumption of the effective functioning of civil aviation in peacetime. The author analyzes the specifics of legal regulation of labor of aviation employees and makes conclusions about its differentiation due to the specifics of the labor function of aviation personnel, which is associated with the risks of operating air transport as an object of high risk and responsibility for the life and health of air passengers, and safety of baggage, goods and mail. The author made a conclusion that the norms of labor law institutions should be extended to aviation personnel, but at the same time, their labor should be regulated in more detail by the air law norms contained in the Air Code of Ukraine and other regulations (including inernatinal law) which constitute the legal support of the aviation industry, in particular, the activities of employees of the aviation sector of the economy.